2018
DOI: 10.1146/annurev-micro-090817-062607
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the Definition of Bacterial Small RNAs: Characteristics and Mechanisms of Action

Abstract: The first report of trans-acting RNA-based regulation in bacterial cells dates back to 1984. Subsequent studies in diverse bacteria unraveled shared properties of trans-acting small regulatory RNAs, forming a clear definition of these molecules. These shared characteristics have been used extensively to identify new small RNAs (sRNAs) and their interactomes. Recently however, emerging technologies able to resolve RNA-RNA interactions have identified new types of regulatory RNAs. In this review, we present a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 109 publications
1
83
0
1
Order By: Relevance
“…Subsequently, numerous chromosomally encoded so-called small RNAs (sRNAs) were discovered and are part of a large repertoire of post-transcriptional regulators in all bacteria and archaea (Beisel & Storz, 2010;Gottesman & Storz, 2011;Barquist & Vogel, 2015;Wagner & Romby, 2015;Holmqvist & Wagner, 2017). Bacterial sRNAs can promote translational activation or, more frequently, repression (Papenfort & Vanderpool, 2015;Wagner & Romby, 2015;Carrier et al, 2018). A striking feature involves targeting of multiple genes within the same network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, numerous chromosomally encoded so-called small RNAs (sRNAs) were discovered and are part of a large repertoire of post-transcriptional regulators in all bacteria and archaea (Beisel & Storz, 2010;Gottesman & Storz, 2011;Barquist & Vogel, 2015;Wagner & Romby, 2015;Holmqvist & Wagner, 2017). Bacterial sRNAs can promote translational activation or, more frequently, repression (Papenfort & Vanderpool, 2015;Wagner & Romby, 2015;Carrier et al, 2018). A striking feature involves targeting of multiple genes within the same network.…”
Section: Introductionmentioning
confidence: 99%
“…This relies on properties of transencoded sRNAs: Since many sRNA genes do not overlap with target genes, base-pairing is non-contiguous and limited. Bacterial sRNAs can promote translational activation or, more frequently, repression (Papenfort & Vanderpool, 2015;Wagner & Romby, 2015;Carrier et al, 2018). Furthermore, target mRNAs can become stabilized or undergo facilitated decay (Lalaouna et al, 2013;Papenfort et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria experience various metabolic and stress conditions they need to respond rapidly. Small trans‐acting regulatory RNAs (sRNAs), which frequently but not always are noncoding, have been found at the heart of regulatory pathways that allow bacteria to regulate virulence gene expression, respond to stresses, sense the population density, modulate the cell surface composition, and adjust their metabolism (Carrier, Lalaouna, & Massé, ; Desgranges, Marzi, Moreau, Romby, & Caldelari, ; Holmqvist & Wagner, ; Radoshevich & Cossart, ). Therefore, it is of utmost interest to identify the RNA targets of these sRNAs, as many bacteria express hundreds of different sRNAs from differentially regulated genes.…”
Section: The Challenge Of Identifying the Regulatory Targets Of Bactementioning
confidence: 99%
“…Small regulatory RNAs have been identified in the past years as posttranscriptional regulators (Carrier et al ., ). These regulatory RNAs generally control mRNA translation and stability by direct RNA–RNA base pairing.…”
Section: Introductionmentioning
confidence: 97%
“…Some chromosomal regulators are involved, i.e., ChvE and ChvIG (Huang et al, 1990;Charles and Nester, 1993), but to date, no plasmid regulator has been identified in this crosstalk between plasmid and chromosome. Small regulatory RNAs have been identified in the past years as posttranscriptional regulators (Carrier et al, 2018). These regulatory RNAs generally control mRNA translation and stability by direct RNA-RNA base pairing.…”
Section: Introductionmentioning
confidence: 99%